2021
DOI: 10.1212/cpj.0000000000000928
|View full text |Cite
|
Sign up to set email alerts
|

Acute Amnestic Syndrome and Ischemic Stroke

Abstract: Purposeof Review: Stroke is an uncommon cause of amnesia. We describe in detail three cases of anterograde amnesia and confabulation secondary to acute ischemic stroke and review the available literature.Recent Findings:In our case series, all three patients presented with anterograde amnesia and two of three co-presented with prominent confabulation. These symptoms were recognized in delayed fashion and no patients received IV tPA. Although stroke infarct topology was variable, all three patients had infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The presence of vertigo and right lateral homonymous hemianopsia (due to the concomitant embolic occlusion of left P2-PCA) helped in the diagnosis and localization ( 38 ). Another case, with right fornix and anteromedial right thalamus infarction was attributed to the occlusion of the tubero-thalamic artery due to its peculiar lesions distribution ( 56 ). The memory disturbance was indistinguishable from the other reported cases ( 38 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of vertigo and right lateral homonymous hemianopsia (due to the concomitant embolic occlusion of left P2-PCA) helped in the diagnosis and localization ( 38 ). Another case, with right fornix and anteromedial right thalamus infarction was attributed to the occlusion of the tubero-thalamic artery due to its peculiar lesions distribution ( 56 ). The memory disturbance was indistinguishable from the other reported cases ( 38 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another case, with right fornix and anteromedial right thalamus infarction was attributed to the occlusion of the tubero-thalamic artery due to its peculiar lesions distribution ( 56 ). The memory disturbance was indistinguishable from the other reported cases ( 38 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its occlusion leads to a stereotyped radioclinical image with a Korsakof syndrome and a stroke of the anterior pillars of the fornix. 1,2 Study Funding No targeted funding reported.…”
mentioning
confidence: 99%